Can Citrus varieties affect the soil fungi community? - Melo, Kryssia Gislayne Pinheiro; da Silva, Angélica Ricarte; Yano- Melo, Adriana Mayumi (Comunicata Scientiae, 2016)
Microorganisms are essential for maintaining soil quality, among which stand out the fungi. The association with arbuscular mycorrhizal fungi (AMF) and phosphorous solubilizing fungi (PSF) in its rhizosphere can benefit citrus plants, since these fungi can contribute to an increase in plant development due to the greater availability of water and nutrients. The present study aimed to evaluate if the amount of total fungi, AMF and PSF in the rhizosphere can be affected by the Citrus varieties. Soil samples were collected from the experiment conducted in a randomized block design (RBD) with six Citrus varieties (Page, Pera D9, D12 Pera Pera C21, Pineaple and Ruby). Regarding the evaluated quantitative variables, there was a significant negative simple linear correlation only between the mycorrhizal colonization (MC) and the number of colony forming unit (CFU)/mL of PSF. The number of CFU/mL of soil FPS did not differed statistically between the Citrus varieties rhizosphere, but for total (TF) fungi a significant difference was observed, especially for the ‘Pineaple’, variety that provided higgher mean for the number of CFU/mL, differing from the ‘Page’ variety. All Citrus varieties presented root colonization by AMF and there was a significant difference among the evaluated varieties, however only ‘Rubi’ and ‘Pineaple’ differed from the others. Citrus varieties do not affect PSF quantity nor MC percentual in their rhizosphere but ‘Page’ and ‘Pineaple’ varieties stand out for glomerospores quantity of AMF and TF CFU/mL.